2020
DOI: 10.1111/tpj.14770
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the pathways for foliar water uptake in beech (Fagus sylvatica L.): a major role for trichomes

Abstract: SUMMARY Foliar water uptake (FWU), the direct uptake of water into leaves, is a global phenomenon, having been observed in an increasing number of plant species. Despite the growing recognition of its functional relevance, our understanding of how FWU occurs and which foliar surface structures are implicated, is limited. In the present study, fluorescent and ionic tracers, as well as microcomputed tomography, were used to assess potential pathways for water entry in leaves of beech, a widely distributed tree s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…A recent study examined foliar water uptake pathways in beech (Fagus spp.) using an AgNO 3 precipitation tracer method, where black deposits formed when Ag 1 ions complexed with anions to precipitate as Ag nanoparticles (Schreel et al, 2020). Uptake was found to be highest in trichomes and Ag nanoparticle deposits were observed in subepidermal sclerenchyma cell lumens and interconnecting pit pairs, supporting the results observed here that trichome absorption and redistribution to sclerenchyma fiber cells could be a key ionic foliar pathway.…”
Section: Foliar P Entry Pathwayssupporting
confidence: 83%
“…A recent study examined foliar water uptake pathways in beech (Fagus spp.) using an AgNO 3 precipitation tracer method, where black deposits formed when Ag 1 ions complexed with anions to precipitate as Ag nanoparticles (Schreel et al, 2020). Uptake was found to be highest in trichomes and Ag nanoparticle deposits were observed in subepidermal sclerenchyma cell lumens and interconnecting pit pairs, supporting the results observed here that trichome absorption and redistribution to sclerenchyma fiber cells could be a key ionic foliar pathway.…”
Section: Foliar P Entry Pathwayssupporting
confidence: 83%
“…In the current work, we first describe the thick‐walled structures composing the multicellular peltate hairs, which project pectins to the external part, suggesting their involvement in the initial water capture when condensation happens in the abaxial side. A few reports have revealed the presence of pectins in trichomes, such as species from semi‐arid forests like Combretum leprosum (Pina et al, 2016), the tropical species Drymis brasiliensis (Eller, Lima, & Oliveira, 2013) or in the trichomes of Fagus (Schreel, Leroux, et al, 2020). In addition, we revealed that both epidermal and spongy mesophyll cells show a high concentration of un‐esterified pectins in their cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…Xerophilous plants that thrive in these ecosystems exhibit anatomical adaptations that reduce rates of water loss, such as smaller leaves, lower stomata index and impermeable coating structures, like cuticles (see Shields, 1950). Surprisingly, some of the structures that prevent evaporative water loss may also facilitate the uptake of atmospheric water condensed on the leaf surface, decoupling the water status of the canopy from soil water availability (Benzing, Seemann, & Renfrow, 1978; Gouvra & Grammatikopoulos, 2003; Schreel et al, 2020; Schreel & Steppe, 2019; Schreel, van de Wal, Hervé‐Fernandez, Boeckx, & Steppe, 2019; Schreel, von der Crone, Kangur, & Steppe, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Water may be absorbed through parallel pathways, including the cuticle/wax layer of ordinary epidermal cells, trichomes or guard cells, and stomatal or hydathode pores (Fernández and Eichert 2009;Martin and von Willert 2000;Schreel et al 2020). Cuticular water uptake was found to be a very slow process involving fluxes in both liquid and vapor phases (Schreiber and Schönherr 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, studies evaluating stomatal FWU have provided divergent results. Water dissolved solutes or suspended particles applied to the leaf surface were either not observed to penetrate stomata (Eller et al 2016;Schreel et al 2020), found on the walls of stomatal pores (Arsic et al 2020;Li et al 2018), or on mesophyll cells lining the substomatal cavity (˜43 nm diameter suspended particles; Eichert et al 2008). It is argued that stomatal anatomical and physico-chemical features prevent liquid water entry into the pore, unless it is forced by an external pressure or water surface tension and cuticular hydrophobicity are reduced by the action of surfactants or other substances such as deliquescent particles or bacteria present along the pores (Burkhardt et al 2012;Eichert et al 2008;Schönherr and Bukovac 1972).…”
Section: Introductionmentioning
confidence: 99%